Nigerian Higher Education Research and the Challenges of Sustainable Development - Kola, Aina, Jacob; Opeyemi, Abdulrahman, Abdulgafar; Sunday, Olanipekun, Sola; Tayo, Olaoye, Oluwaseun (American Journal of Creative Education, 2021)
This is a review paper focusing on research in Nigerian higher education and the impacts on the sustainability of Nigeria as a nation. This article considered research as critical to the development of any country. However, research in Nigerian universities is not encouraging because of some challenges: inadequate facilities, funds, and corruption. Research facilities in universities are not adequate for research and postgraduate studies. The little available funds in universities for research are mismanaged due to corruption. Postgraduate supervision in Nigerian universities is marred with corruption, laziness, and the attrition rate is high. It was argued that the difficulties impact the sustainable development of the country. The paper concludes with suggestions of ways forward; among these is the overhauling of Nigerian universities' postgraduate programs. The university doctoral studies must be reformed to ensure that the supervision of students follows international standards. The university management should not leave doctoral students at the mercy of the supervisor. There should be a Memorandum of Understanding (MoU) between the supervisor and supervisee monitored by university management. Violators, students, or lecturers of the MoU agreement should be adequately sanctioned.